ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM Dr. ABDUL RIVAI - Zulkifli, Zulkifli (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The purpose of this study was to analyze the influence of each dimension of service quality on the level of satisfaction of inpatients which dimensions of service quality are more dominant in influencing the level of satisfaction of inpatients The analytical tool in question is: validity test and reliability test, multiple linear regression analysis, coef icient of determination, t test and F test. Based on the results of the analysis, it can be seen that the dimensions of direct evidence (tangibles) have a significant ef ect on the level of satisfaction of inpatients at Dr. Abdul Rivai General Hospital, while reliability, responsiveness, assurance and attention have no significant ef ect. Tangibles, reliability, responsiveness, assurance and attention can provide a positive and significant influence together or simultaneously on patient satisfaction at Dr. Abdul Rivai General Hospital. The most dominant dimension of influence on the satisfaction of hospitalized patients at Dr. Abdul Rivai General Hospital is a dimension of direct evidence (tangibles), with a regression coef icient of 0.965 or 96.5%. The coef icient of determination or R Square is 97.4%, while the remaining 2.6% is influenced by other factors besides the five dimensions of service quality